(untitled) (Historia, 2021)
This book is recommended for the average South African or tourist who would like to know more about the importance of the Mapungubwe cultural landscape and how it fits into the puzzle of the early prehistory of southern Africa. The social, cultural and political developments at Mapungubwe, which is situated on...